A Multilevel Person-Centered Examination of Teachers' Workplace Experiences: Replication and Extension With Links to Instructional Support and Achievement - Collie, Rebecca J.; Martin, Andrew J.; Morin, Alexandre J. S.; Malmberg, Lars-Erik; Sammons, Pamela (Frontiers in Psychology, 2021)
In a replication and extension of an earlier study, we relied on person-centered analyses to identify teacher (Level 1) and school (Level 2) profiles based on teachers' experiences of job demands (barriers to professional development, disruptive student behavior), job resources (teacher collaboration, input in decision-making), and personal resources (self-efficacy). We examined data from 5,439 teachers working in 364 schools in Australia and 2,216 teachers working in 149 schools in England. Latent profile analysis revealed six teacher profiles: Low-Demand-Flourisher (11%), Mixed-Demand-Flourisher (17%), Job-Resourced-Average (11%), Balanced-Average (14%), Mixed-Resourced-Struggler (11%), and Low-Resourced-Struggler (36%). Two school profiles were identified: an Unsupportive school profile (43%) and a Supportive school profile (57%). Several significant relations between these profiles and teacher/school characteristics and work-related outcomes were also identified at both levels. Although our results generally replicated prior findings, some differences were also observed, possibly as a results of recent changes in policies regarding in teacher support and accountability. Next, we extended prior work using a subsample of the Australian teachers for whom we had matching student data. This second set of results revealed that schools with a greater proportion of low-SES students were more likely to present an Unsupportive school profile. Moreover, the Supportive school profile was associated with higher levels of student-reported instructional support and school-average achievement in reading, mathematics, and science.